Minimally invasive treatment of multiple complications of pancreatitis - R. G. Avanesyan; M. P. Korolev; L. Z. Hafizov; R. A. Movsesian; A. V. Klimov; G. R. Avanesyan (Вестник хирургии имени И.И. Грекова)
A clinical case of multiple complications of pancreatitis associated with intraductal pancreatic hypertension with the formation of a cyst of the head and body of the pancreas and, as a result, biliary hypertension in a 55-year-old patient is presented. A phased minimally invasive treatment of pancreatitis complications is shown using original operations developed in the clinic aimed at internal drainage of the cavity of the pancreatic cyst associated with the duct and restoration of the pancreatic duct with stricture of the terminal department. An original method of removing a foreign body and the lumen of the pancreatic duct using minimally invasive surgery is also presented.